The relationship between creativity, identity, place, and community resilience: the renaissance of Clarksdale, Mississippi, United States - Waddell, Terrie (Creativity Studies, 2021)
This paper examines the relationship between creativity, identity, and place for the small economically challenged Delta City, Mississippi of Clarksdale, United States, a once prosperous manufacturing and farming community. Promoted as the Delta’s epicenter of blues music, over the last twenty years key business stakeholders in the city’s renaissance have been committed to developing local and international awareness of Clarksdale’s historic architecture, culture and blues heritage. It was not until 2008 when economist and town planner John C. Henshall formulated the Downtown Clarksdale Action Plan for Economic Revitalization that the city secured a comprehensive guide to growth. The plan was designed to support downtown infrastructure and tourism through a creatively based strategy, dependent on the tourism potential of blues performances and the imaginative efforts of those invested in the ongoing renewal project. Drawing on incentives aligned with the plan’s objectives, and seven semi-structured interviews with local entrepreneurs and revitalization participants, this paper examines the connection between collaborative creativity, collective identity, connection to place, and community resilience.